THE ROLES OF INVESTIGATOR IN IMPLEMENTING DIVERSION ON CHILDREN CRIMINAL ACTION - Zakki Mubarok; Achmad Sulchan (International Journal of Law Reconstruction, 2018)
Some efforts were made to overcome internal obstacles: improving coordination among investigators, intensive approaches to witnesses, improving socialization of the Criminal Justice System Law and Child Protection Act. While the efforts to overcome the external obstacles: education, rigorous interrogation, improving facilities and infrastructure and bringing together an understanding of the meaning of recidivist. This research is based on the increasingly widespread criminal cases committed by children that occurred in the jurisdiction of Polrestabes Semarang in particular and in various major cities in Indonesia in general. The results of the research indicate that: (1) The role of the investigator in the diversion implementation of child crime cases, namely the internal roles among which are coordinating with the community and with various institutions or related parties, upholding the legal system and criminal justice system in accordance with the mandate of the Act, as well as involving police (Investigator) members in training or special education. (2) The constraints faced by the investigators in the diversion implementation of child crime cases are internal constraints: lack of coordination among investigators, lack of legal understanding of witnesses, lack of socialization of the Criminal Justice System Law and Child Protection Law.